Determinant Factors Affecting Performance of Supply Chain in Pulp and Paper Industries During Pandemic Era in Indonesia - et.al, Kis Yoga Utomo (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
One of the important keys for businesses today to be able to compete is to strengthen their supply chain management system.The impact of a pandemic is felt by all types of businesses, the most important unit of business that also feels the impact of the pandemic is how businesses maintain and even improve the performance of their supply chain management and one of the businesses or industries that is sufficiently affected by the pandemic for its supply chain resilience ispulp and paperindustry. The purpose of this study is to improve the performance of the supply chain, especially in the pulp and paper industry in Indonesia during the pandemic. This study uses two independent variables, namely inventory policies and information sharing and one dependent variable, namely supply chain performance. Data collection in the form of a survey using questionnaire media was carried out on 85 practitioners who work in supply chain units such as production, marketing and logistics. Data collection was carried out from July to September 2020. The results of this study are the conclusion that there is a positive and significant effect of inventory policies and information sharing on supply chain performance. The estimated coefficient of inventory policy on supply chain performance is 0.61, while the estimated coefficient of information sharing on supply chain performance is 0.24. The simultaneously effect of the two independent variables on the dependent is 0.72.